2021
DOI: 10.1037/sah0000305
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 public stigma in the context of government-based structural stigma: A cross-sectional online survey of adults in Bangladesh.

Abstract: The state in Bangladesh has instituted a series of policies and practices during the COVID-19 pandemic that reflects structural stigma. Stigma is now considered a complex phenomenon rather than just one set of beliefs. Thus, the level and correlates of stigma toward individuals and households that have become positive with the Coronavirus are of critical interest and importance. This article describes the nature of the Bangladesh government's unusual labeling practices as a structural stigma and examines the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…Misconceptions and lack of knowledge about COVID-19, along with high fear levels of COVID-19, have been confirmed to be associated with more stigmatizing attitudes towards people associated with the context of COVID-19, such as healthcare providers and Asians in the United States [ 18 , 19 , 20 ]. A national online survey in Bangladesh reported that stigmatizing attitudes related to COVID-19 in the general population was significantly associated with marital status, educational level, living conditions, and perception of risk [ 21 ]. Research on public stigma posited that individuals’ perceptions of stigmatized conditions were associated with their cognitive attributions and affective responses [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Misconceptions and lack of knowledge about COVID-19, along with high fear levels of COVID-19, have been confirmed to be associated with more stigmatizing attitudes towards people associated with the context of COVID-19, such as healthcare providers and Asians in the United States [ 18 , 19 , 20 ]. A national online survey in Bangladesh reported that stigmatizing attitudes related to COVID-19 in the general population was significantly associated with marital status, educational level, living conditions, and perception of risk [ 21 ]. Research on public stigma posited that individuals’ perceptions of stigmatized conditions were associated with their cognitive attributions and affective responses [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, certain demographics of stigmatizers are associated with less stigmatizing attitudes toward (suspected) patients and survivors because they reflect higher knowledge about COVID-stigmatizing attitudes toward COVID-19 patients compared with the general population. Another study 70 found that individuals in Bangladesh with lower education backgrounds have higher levels of stigmatizing attitudes toward COVID-19 patients. Studies in Jordan 68 and China 73 also support this conclusion.…”
Section: Stigmatizermentioning
confidence: 98%
“…Demographics. Stigmatizers' demographics have been investigated in the literature 67,68,69,70,71,72,73 . We identified two aspects highlighting the influence of stigmatizers' demographics: (1) certain demographics of stigmatizers are associated with less stigmatizing attitudes toward (suspected) patients and survivors because they reflect higher knowledge about COVID-19 (e.g., higher education, and healthcare occupations versus general public), and (2) certain demographics of stigmatizers are associated with more stigmatizing attitudes toward (suspected) patients and survivors because they reflect lower resources (e.g., rural versus urban residence) and higher risk of COVID-19 infection (e.g., regions close to the origin location of COVID-19, and old age).…”
Section: Stigmatizermentioning
confidence: 99%
See 2 more Smart Citations